Peran Kemitraan Sekolah Dalam Penguatan Employability Skills Siswa Sekolah Menengah Kejuruan (SMK): A Systematic Literature Review - Srinirmala Nindya Atmaka; Sultoni Sultoni; Juharyanto Juharyanto (Varied Knowledge Journal, 2026)
Abstract: This study aims to systematically analyze the role of school partnerships in strengthening the employability skills of Vocational High School (SMK) students. This issue is important because SMK graduates still experience a relatively high open unemployment rate, indicating a gap between graduates’ competencies and labor market demands. The study employed a Systematic Literature Review (SLR) method based on the PRISMA 2020 guidelines. Data sources were obtained from the Scopus database covering publications from 2021 to 2026. Through the processes of identification, screening, eligibility, and inclusion, 32 articles met the criteria for analysis. Data were analyzed using a thematic approach. The findings reveal that forms of school–industry partnerships include internships, industrial work practices, dual education systems, work-based learning, curriculum alignment, teaching factory, competency certification, and graduate recruitment. These partnerships positively contribute to the development of students’ technical and non-technical skills, particularly communication, teamwork, discipline, adaptability, problem-solving, and work readiness. Supporting factors for successful partnerships include mutual commitment, proactive school leadership, curriculum relevance, intensive communication, and policy support. Meanwhile, major challenges include limited industrial partners, facility gaps, and teachers’ competencies that have not fully kept pace with industrial development. This study concludes that school–industry partnerships are an important strategy for improving the quality of SMK graduates and strengthening workforce competitiveness. Therefore, the development of adaptive and sustainable partnership models should become a priority in vocational education policy in Indonesia.